2019
DOI: 10.1111/rge.12227
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐in‐biotite thermometry in porphyry copper systems: Challenges to application of the thermometer

Abstract: Empirical geothermometer dealing with Ti solubility in the Fe‐Mg biotites was originally proposed for biotites in graphitic, peraluminous metapelites containing ilmenite or rutile that equilibrated roughly at 4–6 kbar. Given that biotites are abundant in the porphyry copper systems, this geothermometer has frequently been used for the determination of magmatic–hydrothermal temperatures in the porphyry copper systems. Common associations of porphyry copper deposits (PCDs), that is, low Al content of biotite, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The Ti-in-biotite thermometer used here is an empirical thermometer based on the Ti, Fe, and Mg content of biotite and developed for metamorphosed pelite [35]. This thermometer is nonetheless often applied to hydrothermal biotite observed in porphyry systems and it tends to overestimate temperature in such settings [36]. Applying this thermometer to the biotite of the Regnault project returns temperatures mostly between 800 • C and 900 • C for the bulk of samples (Figure 7b).…”
Section: Mineral Chemistrymentioning
confidence: 99%
“…The Ti-in-biotite thermometer used here is an empirical thermometer based on the Ti, Fe, and Mg content of biotite and developed for metamorphosed pelite [35]. This thermometer is nonetheless often applied to hydrothermal biotite observed in porphyry systems and it tends to overestimate temperature in such settings [36]. Applying this thermometer to the biotite of the Regnault project returns temperatures mostly between 800 • C and 900 • C for the bulk of samples (Figure 7b).…”
Section: Mineral Chemistrymentioning
confidence: 99%
“…The thermometer, however, might work for peraluminous granites. For example, Rezaei and Zarasvandi [45] showed that thermometer would overestimate the temperature if biotite grained from the porphyry deposits. The majority of our samples is metaluminous and contains other Ti-bearing mineral phases and no graphite.…”
Section: Mineral Geothermobarometermentioning
confidence: 99%